2019
DOI: 10.1021/acs.est.9b00641
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Generation of Reactive Oxygen Species under Visible Light Irradiation by Adjusting the Exposed Facet of FeWO4 Nanosheets To Activate Oxalic Acid for Organic Pollutant Removal and Cr(VI) Reduction

Abstract: In this work, taking FeWO 4 nanosheets as an example, the activation of oxalic acid (OA) based on facet engineering for the enhanced generation of active radical species was reported, revealing unprecedented surface Fenton activity for pollutant degradation. Density functional theory calculations confirmed the more efficient generation of reactive oxygen species over FeWO 4 nanosheets with the {001} facet exposed (FWO-001) under visible light irradiation compared to the efficiency of FeWO 4 nanosheets with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
68
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 177 publications
(70 citation statements)
references
References 41 publications
2
68
0
Order By: Relevance
“…Moreover, $OH generated in this process is the most important active species according to the trapping experiment. The accumulated h + can oxide the organic substrates directly 60 (reaction (7)).…”
Section: Rsc Advances Papermentioning
confidence: 99%
“…Moreover, $OH generated in this process is the most important active species according to the trapping experiment. The accumulated h + can oxide the organic substrates directly 60 (reaction (7)).…”
Section: Rsc Advances Papermentioning
confidence: 99%
“…Dyes, as the prevalent organic contaminant in wastewater, are widely used in coloring and printing activities in paper, textile, leather, and cosmetic industries. [1][2][3][4] Dyecontaining wastewater can directly destroy the ecological balance of a water body and negatively affect human health. 5,6 It has been found that dyes are difficult to degrade by traditional biological methods owing to their complex structure with high molecular weight and cytotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Then the reaction intermediates were degraded to CO 2 and H 2 O. [27] The holes at the valance band of the NFO nanoparticle have low energy than the standard oxidation potential (1.98 V vs. NHE). Therefore, the VB holes at NFO nanoparticles cannot contribute to the organic pollutant degradation process.…”
Section: Photocatalytic Analysismentioning
confidence: 99%